Α2β1 integrin and RhoA mediates electric field‐induced ligament fibroblast migration directionality. Issue 2 (21st August 2012) - Tsai, Cheng‐Hsien; Lin, Bo‐Jiang; Chao, Pen‐Hsiu Grace
Abstract Guided cell migration is important in tissue development, repair, and engineering. We have previously demonstrated that applied electric fields (EFs) enhanced and directed ligament fibroblast migration and collagen production, depending on EF parameters. Electrical stimulation is widely used for the treatment of pain and to promote wound healing. In orthopaedic practices, applied EFs promote bone healing and ligament repair in vivo. In the current study, stimulation waveforms used in physical therapy for promoting tissue repair were adapted to examine their effects on ACL fibroblast migration. Using different waveform and field strengths, we discovered a decoupling of cell motility and directionality, which suggests disparate mechanisms. Integrin, a major extracellular matrix receptor, polarized in response to applied EFs and controlled cell directionality and signaling. Furthermore, we demonstrated that RhoA is a mediator between integrin aggregation and directed cell migration. Polarization is essential in directed cell migration and our study establishes an outside‐in signaling mechanism for EF‐induced cell directionality. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 322–327, 2013